Abdominal aortic and iliac aneurysm presented as lower limb deep vein thrombosis: case report. Issue 4 (3rd July 2020) - Pazur, Vedran; Dakovic Bacalja, Inga; Cvjetko, Ivan; Borovecki, Ana
Abstract: Introduction : We report a rare case of a symptomatic abdominal aneurysm presented as a lower limb deep vein thrombosis (DVT). Case presentation : A 63-year old male presented to our hospital with a recent progressive onset of the right lower limb swelling and pain. The patient had a history of a previous cardiovascular disease. A Duplex ultrasound was performed, which confirmed a right lower limb DVT extending to the right iliac vein. The patient had a pulsatile abdominal mass. Computed tomography scan of the abdomen showed an abdominal aortic and a right iliac artery aneurysm compressing the thrombosed inferior caval and the right iliac vein. The patient was treated with low molecular weight heparin. After resolution of the DVT on day 3 of hospitalization, a surgery on the abdominal and iliac artery aneurysm was performed. The aneurysm was resected and an aortobifemoral bypass was placed using a Dacron prosthesis. The patient remained to be asymptomatic for 6 months after the surgery. Follow up computed tomography demonstrated a fully patent inferior caval and iliac vein and the absence of the aneurysmal disease. Conclusion : Although rare, our case confirms that the DVT should be considered as a possible symptom of an abdominal aneurysm in selected patients.